Studies of oceanic, atmospheric, cryospheric, and fluvial processes through spectral analysis of seismic noise - Anthony, Robert Ernest, author; Aster, Richard, advisor; Schutt, Derek, committee member; Thompson, David, committee member; Reusch, David, committee member (Colorado State University. Libraries, 2016)
During the past decade, there has been rapidly growing interest in using the naturally occurring seismic noise field to study oceanic, atmospheric, and surface processes. As many seismic noise sources, are non-impulsive and vary over a broad range of time scales (e.g., minutes to decades), they are commonly analyzed using spectral analysis or other hybrid time-frequency domain methods. The PQLX community data analysis program, and the recently released Noise Tool Kit that I co-developed with Incorporated Research Institutions for Seismology’s Data Management Center are used here to characterize seismic noise for a variety of environmental targets across a broad range of frequencies. The first two chapters of the dissertation place a strong emphasis on analysis of environmental microseism signals, which occur between 1-25 s period and are dominated by seismic surface waves excited by multiple ocean-solid Earth energy transfer processes. I move away from microseisms in Chapter 3 to investigate the generally higher frequency seismic signals (> 0.33 Hz) generated by fluvial systems. In Chapter 1, I analyze recently collected, broadband data from temporary and permanent Antarctic stations to quantitatively assess background seismic noise levels across the continent between 2007-2012, including substantial previously unsampled sections of the Antarctic continental interior. I characterize three-component noise levels between 0.15-150 s using moving window probability density function-derived metrics and analyze seismic noise levels in multiple frequency bands to examine different noise sources. These metrics reveal and quantify patterns of significant seasonal and geographic noise variations across the continent, including the strong effects of seasonal sea ice variation on the microseism, at a new level of resolution. Thorough analysis of the seismic noise environment and its relation to instrumentation and siting techniques in the Polar Regions facilitates new science opportunities and the optimization of deployment strategies for future seismological research in the Polar Regions, and in mountain glacier systems. Chapter 2 details the analysis of 23 years of microseism observations on the Antarctic Peninsula to investigate wave-sea ice interactions and assess the influence of the Southern Annular Mode (SAM) on storm activity and wave state in the Drake Passage. The lack of landmasses, climatological low pressure, and strong circumpolar westerly winds between latitudes of 50°S to 65°S produce exceptional Southern Ocean storm-driven wave conditions. This combination makes the Antarctic Peninsula one of Earth's most notable regions of high amplitude wave activity and one of the planet’s strongest sources of ocean-swell driven microseism noise in both the primary (direct wave-coastal region interactions) and secondary (direct ocean floor forcing due to interacting wave trains) period bands. Microseism observations are examined from 1993-2015 from long running seismographs located at Palmer Station (PMSA), on the west coast of the Antarctic Peninsula, and from the sub-Antarctic East Falkland Island (EFI). These records provide a spatially integrative measure of Southern Ocean amplitudes and of the degree of coupling between ocean waves and the solid earth with and without the presence of sea ice (which can reduce wave coupling with the continental shelf). A spatiotemporal correlation-based approach illuminates how the distribution of sea ice influences seasonal primary and secondary microseism power. I characterize primary and secondary microseism power due to variations in sea ice, and find that primary microseism energy is both more sensitive to sea ice and more capable of propagating across ocean basins than secondary microseism energy. During positive phases of the SAM, sea ice is reduced in the Bellingshausen Sea and overall storm activity in the Drake Passage increases, resulting in strongly increased microseism power levels. The field of fluvial seismology has emerged during the past decade, with seismic recordings near fluvial systems showing potential for a continuous, inexpensive, and non-invasive method of measuring flow and, in some cases, bed-load transport, in streams and rivers. In Chapter 3, I extend this research to the South Fork of the Cache la Poudre River in Northern Colorado where I deployed a small seismoaccoustic array while simultaneous measurements of discharge, suspended sediment concentrations, and precipitation were obtained. By placing seismometers within unprecedented proximity to the channel (~ 1 m, and during some time periods submerged), I found a broad range of frequencies excited by discharge, including novel, low-frequency (< 1 Hz) signals. After calibrating horizontal seismic power with flow rates over the course of a rainstorm event for individual sensors, I show that horizontal seismogram power in the 0.33-2 Hz band can be used to accurately invert for fluvial discharge with simple regressions, once a site is properly calibrated to a traditional hydrograph. These signals likely arise from local sensor tilt as the seismometer is directly forced by channel flow and show promise for augmenting seismic monitoring of fluvial systems by introducing a technique to estimate discharge rates from outside the channel with easily deployed noninvasive instrumentation.